Natural resources sector : review and identification of opportunities for commodity-based trade and development (UN New YorkUS, 2014)
Reviews and identifies opportunities for commodity-based trade and development, with a focus on the natural resources sectors, including energy, minerals and metals, in accordance with the Accra Accord and the Doha Mandate.
Note by the UNCTAD Secretariat